Satisfaction And Commitment In Dating Relationship Among College Students In Pulau Pinang - Shin, Yong Ken (2019)
Dating relationship is an important topic in relationship research and had been widely studied in Western context. This study focuses on dating relationship in Malaysia. Personal reasons for dating, factors associated with dating, relationship satisfaction and commitment were examined among 106 college students who were in a dating relationship at the time of the data collection. This study aimed to identify the reasons and factors for dating among college students in Malaysia and to examine how the reasons and factors predict relationship satisfaction and commitment.